Overview of Palliative Care Service in Hong Kong - Hilary H.L Yee; Ben Y.F Fong; Tommy K.C Ng (ACHSM, 2020)
Palliative care service is a growing trend for patients with terminal illnesses. The purpose of palliative care is to improve the quality of life for the patients and their family by providing comprehensive care such as symptoms control, pain relief and counselling support. More and more people prefer to spend the final stage of their life in a comfortable environment with adequate care. However, Hong Kong is only ranked 22 in 2015 Quality of Death Index, and hence enhancement of palliative care service is much needed. This review paper aims to evaluate the current resources and development of palliative care service in Hong Kong and suggest improvement of the service. This study reveals that the system in Hong Kong lacks a comprehensive policy, thus limiting organisations to provide the service to small-scale operations and resulting in fragmentation of the co-operation between the public and private sectors. Factors such as professional training, community engagement, culture and financial issues are affecting the development and adequacy of palliative care service.